2022
DOI: 10.2196/24111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Using Virtual Reality–Supported Exercise Therapy for Upper Extremity Motor Rehabilitation in Patients With Stroke: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background In recent years, efforts have been made to implement virtual reality (VR) to support the delivery of poststroke upper extremity motor rehabilitation exercises. Therefore, it is important to review and analyze the existing research evidence of its effectiveness. Objective Through a systematic review and meta-analysis of randomized controlled trials, this study examined the effectiveness of using VR-supported exercise therapy for upper extremit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 104 publications
1
47
0
Order By: Relevance
“…The improvement in ROM is reported in both groups however group A demonstrated a comparatively higher degree of freedom supporting the findings of Then et al who reported composite significance in improving finger ROM by using gamification induced with a mobile device post metacarpal fracture [14]. In 2022, Chen et al reported that VR-supported therapy had a significant improvement in ROM [15].…”
Section: Discussionsupporting
confidence: 68%
“…The improvement in ROM is reported in both groups however group A demonstrated a comparatively higher degree of freedom supporting the findings of Then et al who reported composite significance in improving finger ROM by using gamification induced with a mobile device post metacarpal fracture [14]. In 2022, Chen et al reported that VR-supported therapy had a significant improvement in ROM [15].…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, it would be useful to develop a safe, easy, and clinically feasible treatment technique to reduce upper-limb disability. There are several promising treatment options available for upper-limb stroke rehabilitation, such as cross education [ 8 ], constraint-induced movement therapy [ 9 ], virtual reality therapy [ 10 ], functional electrical stimulation [ 11 ], robotic therapy [ 12 ], anodal transcranial direct current stimulation [ 13 ], and motor imagery [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include websites, diagnostic and monitoring devices, smartphone apps, virtual reality systems, telephone and video calls, and electronic messages that provide health information or services [8][9][10]. Researchers have implemented these eHealth interventions into a range of health care activities, including teleconsultation [11,12], remote patient monitoring [13], self-management of diseases [14][15][16], disease rehabilitation [17], and disease prevention [18]. Promising results have emerged from these studies, which showed that eHealth interventions could facilitate the delivery of health care and improve patient outcomes [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have implemented these eHealth interventions into a range of health care activities, including teleconsultation [11,12], remote patient monitoring [13], self-management of diseases [14][15][16], disease rehabilitation [17], and disease prevention [18]. Promising results have emerged from these studies, which showed that eHealth interventions could facilitate the delivery of health care and improve patient outcomes [9][10][11][12][13][14][15][16][17]. It has also been shown that eHealth enables consumers to easily obtain information about health issues for decision-making, which could lead to more effective care, patient empowerment, and time savings [8,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%